Human Sperm Counting Efficacy of the Shukratara Chamber Versus the Makler Chamber - Jay, V.; Sivalingarajah, R.; Balagobi, B.; Sivakumar, A.; Ramesh, N.; Jeyendran, R.S. (Researchgate, 2024)
Purpose: The objective of this study was to compare the sperm counting efficacy of the less expensive Shukratara sperm counting chamber with the widely accepted Makler counting chamber. Methods: Frozen sperm samples from 70 men were thawed and the sperm concentration determined using both counting cham- bers respectively. Capsule: The counting efficacy between less expensive Shukrata- ra sperm counting chamber and Makler sperm counting chamber using frozen thawed sperm was found to be similar. Results: The mean ± standard deviation (67.9 ± 5.8 VS 59.0 ± 5.9; 106 /mL) and fifth percentile ± 95 % confidence interval between the two respective chambers for sperm concentration determined. There was no significant difference (p > 0.05) between the two sperm concentrations were found. Conclusions: The mean ± standard deviation (61.9 ± 72.9 VS 62.1 ± 60.0; 106 /mL) and fifth percentile ± 95 % confidence in- terval (67.9 ± 5.8 VS 59.0 ± 5.9; 106 /mL) between the two respec- tive chambers for sperm concentration determined. There was no significant difference (p>0.05) between the two sperm concentra- tions were found.
Keywords: Shukratara chamber; Makler chamber; Sperm count- ing; Efficacy